Correlation of blood lead level and intelligence quotient in children - Lilian Gunawan; Nurhayati Masloman (Paediatrica Indonesiana, 2014)
Background Lead poisoning is a source of health problems inhumans. A chronic complication oflead poisoning in children ispermanent intellectual impairment.Objective To assess for a correlation of blood lead levels andintelligence quotient (IQ) in children.Methods A cross-sectional study was performed in children aged6 to 8 years in th e Talawaan (a rural area) and Wenang (an urbanarea) Distticts, North Sulawesi, from April to July 2012. Blood leadlevels were measured using the graphite furnace atomic absorptionspectrometry technique; and intelligence was meas ured with theWechsler Intelligence Scale for Children-Indonesian version.Results There were 50 subjects from the Talawaan District and 54subjects from the Wenang Disttict in this study. The mean bloodlead level in the Talawaan District subjects was significantly higherthan that of the Wenang Disttict subjects [25.8 (SD 16.98) Î¼gidLvs 11.4 (SD 13.81) Î¼gidL, respectively; (P<0.001)]. There was aweak negative correlation between blood lead level and IQ in theTalawaan Disttict children (P= 0.038; r= -0.3). As such, there wasa 0.05 IQ point decrement associated with each increase of 1 Î¼ gidLin blood lead level in Talawaan District children. However, therewas no correlation between blood lead level and IQ in the WenangDisttict children (P=0.42; r =0.03).Conclusion There is a weak negative correlation between bloodlead level and IQ in children living in a rural area, howevei; thiscorrelation is not found in children living in an urban area.